2011
DOI: 10.1111/j.1556-4029.2011.01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Contamination by Controlled Substances in Euro Banknotes from the Spanish Archipelago of the Canary Islands

Abstract: The social problems of drug abuse are a matter of increasing global problem. Nowadays, international agencies need fresh methods to monitor trends of the use of illicit drugs. In this sense, small amounts of drugs are transferred to banknotes and they could be detected and quantified. An analytical procedure based upon extraction with organic solvent, liquid chromatography separation, and mass spectrometric detection allowed the identification of 21 drugs and metabolites in 120 used Euro banknotes collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It has been documented that a significant proportion of paper currency in general circulation is contaminated with cocaine [2][3][4][5][6][7][8]. Adherence of cocaine to the banknote can be due to surface contamination and entrapment of drug crystals between fibres of the note [9], while indirect transfer of cocaine is possible through contact with other notes or bank sorting machines [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that a significant proportion of paper currency in general circulation is contaminated with cocaine [2][3][4][5][6][7][8]. Adherence of cocaine to the banknote can be due to surface contamination and entrapment of drug crystals between fibres of the note [9], while indirect transfer of cocaine is possible through contact with other notes or bank sorting machines [10].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews or other papers covering the detection of drugs, e.g., via the testing of hair [ 6 , 7 , 8 , 9 ], the use of molecularly imprinted polymers [ 10 , 11 ], aptamers [ 12 ], ion mobility spectrometry [ 10 , 11 ], mass spectrometry [ 13 , 14 , 15 , 16 , 17 ], hybrid methods [ 18 ], electrochemical methods [ 19 , 20 ], biosensors [ 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], and immunoassays [ 35 , 36 , 37 ] have been published. Quite popular in analytical chemistry was the detection of cocaine on banknotes [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. It can be concluded that cocaine detection is still an active field of research and development.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews or other papers covering the detection of drugs, e.g via the testing of hair [3][4][5][6], the use of molecularly imprinted polymers [7,8], aptamers [9], ion mobility spectrometry [10,11], mass spectrometry [12][13][14][15][16], hybrid methods [17], electrochemical methods [18,19], biosensors [9,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] and immunoassays [34][35][36] have been published. Quite popular in analytical chemistry was the detection of cocaine on banknotes [37][38][39][40][41][42][43][44]. It can be concluded that cocaine detection is still an active field of research and development.…”
Section: Introductionmentioning
confidence: 99%